Fatigue and Tensile Characteristics for Composite Materials Used in Prosthetic Socket - Salim Khamees, Zuhair; Khalil, Asmaa Shawqy (Iraqi Journal of Physics, 2023)
In this research, the use of natural materials like wool and cannabis as intermediate reinforcement for prosthetic limbs due to their comfort, affordability, and local availability was discussed. As part of this study on below-the-knee (BK) prosthetic sockets, two sets of samples were made using a vacuum method. These sets were made of natural fiber-reinforced polymer composites with lamination 80:20: group (Y) had 4 perlon, 1 wool 4 perlon, and group (G) had 4 perlon, 1 cannabis 4 perlon. The two groups were compared with a socket made of polypropylene. Tensile testing was used to determine the mechanical characteristics of the socket materials. The Y group has a yield stress of 17 MPs, an ultimate strength of 18.75 MPa, and an elastic modulus of 4.021 GPa, while for the G group, these values are 12.75 MPa, 18.84 MPa, and 4.076 GPa, respectively. The fatigue test was used to evaluate the failure characteristics of the socket. An F-socket was utilized to test the interface compression between both the limb and the socket. For the Tekscan sensor, the calculated pressure in the medial region is 350 K Pa, while it is 330 KPa in the posterior region. Solid Works software was used to draw a prosthetic socket for the numerical study. The failure safety agent for the composite material for group Y was 1.26. The finite element method (ANSYS Workbench 14.5) was used to look at the fatigue characteristics to detect the maximum stress, safety factor, and total deformation.